2022
DOI: 10.1002/anie.202211945
|View full text |Cite
|
Sign up to set email alerts
|

Isoxazole Nucleosides as Building Blocks for a Plausible Proto‐RNA

Abstract: The question of how RNA, as the principal carrier of genetic information evolved is fundamentally important for our understanding of the origin of life. The RNA molecule is far too complex to have formed in one evolutionary step, suggesting that ancestral proto-RNAs (first ancestor of RNA) may have existed, which evolved over time into the RNA of today. Here we show that isoxazole nucleosides, which are quickly formed from hydroxylamine, cyanoacetylene, urea and ribose, are plausible precursors for RNA. The is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(63 reference statements)
0
7
0
1
Order By: Relevance
“…Many of the prebiotic precursors do not present a complicated chemical structure and, consequentially, are susceptible to being detected in the interstellar medium (ISM). For example, recent astronomical surveys have found 1-2-ethenediol ((C 2 H 2 O) 2 (Rivilla et al 2022) a key molecule in the synthesis of sugars, ethanolamine (NH 2 CH 2 CH 2 OH) (Rivilla et al 2021) a key molecule in the synthesis of phospholipids, and the molecule subject of this study, hydroxylamine NH 2 OH (Rivilla et al 2020), which is assumed to be crucial E-mail: molpeceres@astron.s.u-tokyo.ac.jp in forming amino acids and RNA nucleotides (Sakurai & Yanagawa 1984;Snow et al 2007;Becker et al 2019;Xu et al 2022).…”
Section: Introductionmentioning
confidence: 91%
“…Many of the prebiotic precursors do not present a complicated chemical structure and, consequentially, are susceptible to being detected in the interstellar medium (ISM). For example, recent astronomical surveys have found 1-2-ethenediol ((C 2 H 2 O) 2 (Rivilla et al 2022) a key molecule in the synthesis of sugars, ethanolamine (NH 2 CH 2 CH 2 OH) (Rivilla et al 2021) a key molecule in the synthesis of phospholipids, and the molecule subject of this study, hydroxylamine NH 2 OH (Rivilla et al 2020), which is assumed to be crucial E-mail: molpeceres@astron.s.u-tokyo.ac.jp in forming amino acids and RNA nucleotides (Sakurai & Yanagawa 1984;Snow et al 2007;Becker et al 2019;Xu et al 2022).…”
Section: Introductionmentioning
confidence: 91%
“…Um die Beladung des RNA-Strangs ON2 mit Ala weiter zu belegen, führten wir einen enzymatischen Verdau des isolierten RNA-Produkts ON1g zu den Nukleosiden durch und analysierten den Verdau mit Hilfe der entsprechenden Nukleosid-Referenzverbindungen mittels HPLC-MS. [66] Wir setzten ON1g mit einem nucleoside digestion mix bei 37 °C für 2 h um. Die Analyse der erhaltenen Nukleosidmischung zeigte zwei Signale, die 1 g (a 6 A) und Adenosin in einem Verhältnis von ca.…”
Section: Präbiotische Beladung Von Rna Mit Aminosäurenunclassified
“…We recently showed that the nucleoside C can form directly in RNA from embedded IO3 ribofuranosides, which allowed us to show that IO3-precursor RNAs are an extant model for a proto-RNA that could have preceded canonical RNA. [18] In order to investigate if this direct "in-RNA" transformation is also possible with IO5 to generate U and to study if C and U can form simultaneously from IO3 and IO5-containing proto-RNA, we prepared the IO3-phosphoramidite building blocks for solid phase RNA synthesis. This was achieved following a synthetic pathway outlined in Scheme 1A.…”
Section: Formation Of C and U From Isoxazoles Directly In Rnamentioning
confidence: 99%
“…[17] The compound embedded as a riboside in RNA was able to perform the cascade reaction to C (Figure 1A). [18] Although this chemistry provides access to C, the second important pyrimidine nucleoside of the genetic code U is in this scenario only available via the hydrolysis of C. This, however, is a slow reaction particularly if the C is embedded in RNA. [19,20] In order to solve this problem and to find a common prebiotically plausible route to both pyrimidines C and U, we investigated the starting point of the IO-based chemistry, namely the reaction of cyanoacetylene (1) with hydroxylamine (2) in greater detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation